FACTORS THAT CAN INFLUENCE SUBSCRIBE INTENTION ON KOMPAS.ID MODERATED BY SUBSCRIPTION TYPES - Zendrato, Bernadus Orudu Richard; Sadat, Andi Muhammad; Monoarfa, Terrylina Arvinta (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the effect of enjoyment, price value, and ubiquity on the subscription intention of Kompas.id users, and see the moderating role of subscription types (basic and premium) in the relationship. A quantitative approach was used with a survey method, involving 400 Kompas.id user respondents in the Jabodetabek area. The data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The results showed that enjoyment and price value had a significant effect on subscription intention. Ubiquity has a significant effect on subscription intention. Moderation tests show that subscription types only moderates the relationship between ubiquity and subscribe intention, while it does not moderate the relationship between enjoyment and price value on subscribe intention. The findings provide theoretical and practical implications for digital marketing strategies in increasing subscription conversion through enjoyable user experience, value for money, and ease of access.